AKIBAT HUKUM PELANGGARAN KODE ETIK NOTARIS DALAM MEMPROMOSIKAN DIRI MELALUI MEDIA SOSIAL - Saraswati, Harsinta; Damaiyanti, Nandini Intan; Rokhyati, Sri (PALAR (Pakuan Law review), 2024)
Abstract The use of social media to publish and promote notary services is considered to be in violation of the code of ethics and must comply with applicable laws. To overcome this violation, supervision of notaries is applied. The approach method used in this article is a normative juridical approach. Based on the results of the author's research that notaries commit violations when promoting and self-publishing on social media, namely Instagram, this notary is not allowed because this prohibition is a result of the position of the notary profession as a public official in accordance with the notary code of ethics. As enforcers of the notary code of ethics, the Notary Honor Council and the Notary Supervisory Council have the task of ensuring that notaries understand the implementation of the code of ethics properly. The Supervisory Council has the authority to provide guidance and supervision of Notaries and to conduct examinations of alleged violations of the behavior and implementation of the office of Notary. Keywords: social media, code of ethics, Notary. Abstrak Penggunaan media sosial untuk publikasi dan mempromosikan jasa notaris, dinilai sangat melanggar kode etik dan harus mematuhi aturan hukum yang berlaku. Untuk mengatasi adanya pelanggaran ini adalah diterapkan adanya pengawasan terhadap notaris. Metode pendekatan yang digunakan dalam artikel ini yaitu pendekatan yuridis normatif. Berdasarkan hasil penelitian penulis bahwa notaris melakukan pelanggaran apabila melakukan promosi dan publikasi diri di sosial media yaitu instagram, pelanggaran ini merupakan konsekuensi dari kedudukan profesi notaris sebagai pejabat umum sesuai dengan kode etik notaris. Sebagai penegak Kode etik notaris, Dewan Kehormatan Notaris dan Majelis Pengawasan Notaris memiliki tugas yaitu telah dipastikan supaya notaris paham pada pelaksanaan kode etik dengan sebaik-baiknya. Majelis Pengawas berwenang melakukan pembinaan dan pengawasan terhadap Notaris serta melakukan pemeriksaan terhadap dugaan pelanggaran perilaku dan pelaksanaan jabatan Notaris. Kata Kunci : media sosial, kode etik, Notaris.